Practical epistemology: the role of peer review in organizing scientific research - A. V. Shestopal (MGIMO University Press, 2014)
The article considers peer review as the main procedure for demarcating scientific knowledge from other kinds thereof, which do not meet the criteria set for research results. The authors examine the history of peer review, which has first been used in early scientific journals and then has become one of the key approaches to distributing funds for research in science foundations, such as the U.S. National Science Foundation. The article also considers the role of peer review in the legal process, wherein observance of this procedure can be seen as the main criteria, which separates scientific evidence from mere testimony. The description of the main elements of the peer review procedure is based on the "Statement of principles for scientific merit review" the summary of the results of the Global Summit on Merit Review, which brought together heads of science funding organizations from more than 50 countries. The Statement listed the following principles: expert assessment, transparency, impartiality, appropriateness, confidentiality, integrity and ethical considerations. Although these principles are seen as a way to guarantee efficient peer review one has to consider the peculiarities of a particular research area, first of all the differences between social and natural sciences. Accordingly the article gives an overview of key traits of peer review in the social sciences and humanities. The authors also consider the main procedural elements - preparation of individual reviews, consideration by panels, anonymity of reviewers. Finally the article addresses the problems of peer review such as non-transparent process, elitism in selecting reviewers, conservativeness of decisions, and possible ways of handling these problems.